The Potential of Pencak Silat from the Perspective of Positive Youth Development (PYD) - Fatih Al Fiqri; Carsiwan; Marisa Noviyanti Fajrah Ilsya (Universitas Negeri Semarang, 2026)
This study investigates the effect of Pencak Silat extracurricular activities integrated with the Positive Youth Development (PYD) framework on adolescent development. The research is motivated by the growing need to promote character formation and life skills among youth through structured, sport-based educational interventions. A quantitative method employing a quasi-experimental design with a pretest–posttest control group format was utilized. The sample consisted of 26 adolescents aged 14–18 years, divided equally into an experimental group, which received PYD-integrated Pencak Silat training, and a control group, which participated in conventional training without explicit PYD components. Data were collected using the Positive Youth Development Inventory (PYDI), a validated and reliable instrument measuring six core PYD dimensions: competence, confidence, connection, character, caring, and contribution. Statistical analysis revealed a significant difference between the experimental and control groups (p < 0.05), with the experimental group demonstrating superior posttest outcomes. Additionally, the normalized gain (N-Gain) analysis yielded a mean score of 0.4258, categorized as moderate, indicating a measurable improvement in PYD dimensions following the intervention. These findings suggest that the integration of PYD principles within Pencak Silat training contributes significantly to adolescents’ holistic development. Beyond its role as a physical activity, Pencak Silat represents a culturally embedded pedagogical medium capable of fostering character education and social competence. The study underscores the potential of value-based traditional sports programs in educational contexts and recommends further research with larger sample sizes and extended intervention durations to enhance generalizability and robustness of findings.